2022
DOI: 10.1002/lsm.23610
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microwave thermolysis energy levels on patient‐reported outcomes for axillary hyperhidrosis and osmidrosis

Abstract: Objective Microwave thermolysis (MWT) is an emerging treatment for axillary hyperhidrosis reducing both sweat and odor. No prior studies have investigated and compared the different available energy settings of the MWT device. This study evaluated patient‐reported outcome measures (PROMs) for axillary hyperhidrosis and osmidrosis following MWT treatment with two different energy levels. Methods Twenty adults with axillary hyperhidrosis and osmidrosis reported sweat on Hyperhidrosis Disease Severity scale (HDSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The mean DLQI score for preoperative patients was 16.10, whereas for postoperative patients it decreased to 3.30. In the present study, the DLQI scores for postoperative patients in the two groups were significantly decreased compared with the scores for preoperative patients in the two groups and these results were consistent with the results reported by a previous study (31), and the removal of sweat gland and hair follicle tissue is more complete in the experimental group. However, the present results showed recurrence in some patients who still had a grade 2/3 odor degree 6 months after surgery and indicated some protective effect for patients.…”
Section: Discussionsupporting
confidence: 93%
“…The mean DLQI score for preoperative patients was 16.10, whereas for postoperative patients it decreased to 3.30. In the present study, the DLQI scores for postoperative patients in the two groups were significantly decreased compared with the scores for preoperative patients in the two groups and these results were consistent with the results reported by a previous study (31), and the removal of sweat gland and hair follicle tissue is more complete in the experimental group. However, the present results showed recurrence in some patients who still had a grade 2/3 odor degree 6 months after surgery and indicated some protective effect for patients.…”
Section: Discussionsupporting
confidence: 93%
“…A single-session one-pass protocol is adequate, as evidenced by a recent published article's claim that patients were willing to endure a greater degree of transitory local skin reactions from a higher energy setting in exchange for more odor and perspiration reduction. 18 By ensuring the depth of the deep fascia was at least 5 mm in all cases, high-energy treatment with a level 5 setting is safe, and the effect of the treatment is long-lasting. After 1 year, participants still had a significant improvement in AO compared with their pretherapeutic status.…”
Section: Discussionmentioning
confidence: 97%
“…Our study revealed that microwave treatment is an efficient method for treating AO and AH in Asians. A single‐session one‐pass protocol is adequate, as evidenced by a recent published article's claim that patients were willing to endure a greater degree of transitory local skin reactions from a higher energy setting in exchange for more odor and perspiration reduction 18 . By ensuring the depth of the deep fascia was at least 5 mm in all cases, high‐energy treatment with a level 5 setting is safe, and the effect of the treatment is long‐lasting.…”
Section: Discussionmentioning
confidence: 99%